Fatty acid‐binding protein 4 regulates fatty infiltration after rotator cuff tear by hypoxia‐inducible factor 1 in mice. Issue 5 (5th April 2017) - Lee, Yong‐Soo; Kim, Ja‐Yeon; Oh, Kyung‐Soo; Chung, Seok Won
Abstract: Background: Fatty infiltration in skeletal muscle is directly linked to loss of muscle strength and is associated with various adverse physical outcomes such as muscle atrophy, inflammation, insulin resistance, mobility impairments, and even mortality in the elderly. Aging, mechanical unloading, muscle injury, and hormonal imbalance are main causes of muscle fat accumulation, and the fat cells are derived from muscle stem cells via adipogenic differentiation. However, the pathogenesis and molecular mechanisms of fatty infiltration in muscles are still not fully defined. Fatty acid‐binding protein 4 (FABP4) is a carrier protein for fatty acids and is involved in fatty acid uptake, transport, and lipid metabolism. Rotator cuff tear (RCT) usually occurs in the elderly and is closely related with fatty infiltration in injured muscle. To investigate potential mechanisms for fatty infiltration other than adipogenic differentiation of muscle stem cells, we examined the role of FABP4 in muscle fatty infiltration in an RCT mouse model. Methods: In the RCT model, we evaluated the expression of FABP4 by qRT‐PCR, western blotting, and immunohistochemical analyses. Histological changes such as inflammation and fat accumulation in the injured muscles were examined immunohistochemically. To evaluate whether hypoxia induces FABP4 expression, the levels of FABP4 mRNA and protein in C3H10T1/2 cells after hypoxia were examined. Using a transient transfection assay in 293T cells, we assessed the promoter activity of FABP4 by hypoxia‐inducible factors (HIFs). Additionally, we evaluated the reduction in FABP4 expression and fat accumulation using specific inhibitors for HIF1 and FABP4, respectively. Results: FABP4 expression was significantly increased after RCT in mice, and its expression was localized in the intramuscular fatty region. Rotator cuff tear‐induced FABP4 expression was up‐regulated by hypoxia. HIF1α, which is activated by hypoxia, augmented the promoter activity of FABP4, together with HIF1β. Hypoxia‐induced FABP4 expression was significantly decreased by HIF1 inhibitor treatment. Furthermore, in RCT model mice, fat accumulation was remarkably reduced by FABP4 inhibitor treatment. Conclusions: This study shows that RCT induces FABP4 expression, leading to fat accumulation in injured muscle. FABP4 transcription is regulated by the direct binding of HIF1 to the FABP4 promoter in the hypoxic condition induced by RCT. Fat accumulation in injured muscle was reduced by the inhibition of FABP4. Ultimately, in the RCT model, we identified a novel mechanism for fatty infiltration by FABP4, which differs from adipogenic differentiation of muscle stem cells, and we found that fatty infiltration might be regulated by inhibition of HIF1 or FABP4.